PERAN DIGITAL TRANSFORMATION MEMODERSI PENGARUH PUBLIC SERVICE MOTIVATION DAN KEPUASAN KERJA TERHADAP WORK LIFE BALANCE PADA PT. JASA RAHARJA (PERERO) WILAYAH SULAWESI UTARA - Stevan Elisender Miringan; Rahmisyari Rahmisyari; Marten Puyo (Jurnal Ekonomi Ichsan Sidenreng Rappang, 2026)
This study aims to determine the Role of Digital Transformation in Moderating the Influence of Public Service Motivation and Job Satisfaction on Work Life Balance at PT. Jasa Raharja (perero) in North Sulawesi Region. This study uses a quantitative approach with an explanatory research design, data was collected from 62 respondents through a survey and analyzed with Structural Equation Modeling (SEM) via SmartPLS 3.0. The results of the study indicate that public service motivation has no significant effect on work life balance. This result is evidenced by the P Value value greater than the sig value (0.379 > 0.05). Job Satisfaction has a positive and significant effect on work life balance. This result is evidenced by the P Value value smaller than the sig value (0.000 < 0.05). Digital transformation has a positive and significant effect on work life balance. This result is evidenced by the P Value value smaller than the sig value (0.013 < 0.05). Digital transformation plays a moderating role in the relationship between public service motivation and work life balance. This result is proven by the P Value being smaller than the sig value (0.014 < 0.05) and digital transformation cannot play a moderating role in the relationship between job satisfaction and work-life balance. This result is proven by the P Value being greater than the sig value (0.305 > 0.05)